Squamous cell carcinoma of supraglottic larynx with metastasis to all five distal phalanges of left hand - Narendra Kumar; Anjan Bera; Ritesh Kumar; Sushmita Ghoshal; Shabab Lalit Angurana; Radhika Srinivasan (Wolters Kluwer Medknow Publications, 2011)
Subcutaneous metastasis from carcinoma larynx is a rare presentation and to the phalynx is the rarest. We herein describe a case report of carcinoma supraglottic larynx, which is involving all five distal phalanges of left hand with simultaneous metastases to lung and liver. Acrometastasis is an unusual presentation, which might mimic an infectious or inflammatory pathology. The brief report highlights the importance of clinical awareness of metastatic dissemination to unusual sites in the face of increasing cancer survivorship.